A ANALISIS DAMPAK PENGGUNAAN GAWAI/GADGET TERHADAP AKTIVITAS OLAHRAGA SISWA SEKOLAH DASAR - Muhammad Aspar; Taufik Yudi Mulyanto; Galang Pakarti Mahardika; Adib Internareza Paramadina (Jurnal Speed (Sport, Physical Education, Empowerment), 2020)
This study aims to analyze the sports activities of elementary school students due to the use of gadgets. The proliferation of online games in generations Y and Z, there are many opportunities for children to get addicted to it. This study used a descriptive qualitative method for elementary students. This study aims to examine sports activities on the impact of device use on elementary students. Sports activities have an impact on increasing physical ability to perform all daily activities. With uncontrolled use of devices or even in the addiction aspect, it will affect the body's performance to carry out activities.